2007
DOI: 10.1007/s00408-007-9004-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Related Breathing Disorders in Patients with Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and usually fatal lung disease of unknown etiology. The aim of this study was to describe clinical and polysomnographic features of sleep-related breathing disorders (SRBD) and to identify predictors of obstructive sleep apnea (OSA) in IPF patients. Eight hundred fifty-seven patients with IPF were admitted to the Cleveland Clinic from 2001 to 2005. An all-night polysomnogram (PSG) was performed in 18 of them to investigate complaints suggestive of sleep-disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
84
1
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 28 publications
9
84
1
12
Order By: Relevance
“…Prior polysomnographic studies in the mid-1980s demonstrated alterations in sleep architecture and oxygen desaturation, especially during REM sleep, but not OSA, even in morbidly obese patients with ILDs [3,4]. The results of the study by Pihtili et al related to IPF patients are similar to recent studies that report increased incidence of OSA and pointed the need for high clinical suspicion for possible underlying OSA in this population [5][6][7][8]. Prior studies dating back 10-20 years probably underestimated hypopneas by using only thermal sensors and not nasal pressure transducers which are recognized as the sensitive devices for hypopnea detection that represents the majority of the observed respiratory events in IPF patients based on the newer studies.…”
supporting
confidence: 65%
“…Prior polysomnographic studies in the mid-1980s demonstrated alterations in sleep architecture and oxygen desaturation, especially during REM sleep, but not OSA, even in morbidly obese patients with ILDs [3,4]. The results of the study by Pihtili et al related to IPF patients are similar to recent studies that report increased incidence of OSA and pointed the need for high clinical suspicion for possible underlying OSA in this population [5][6][7][8]. Prior studies dating back 10-20 years probably underestimated hypopneas by using only thermal sensors and not nasal pressure transducers which are recognized as the sensitive devices for hypopnea detection that represents the majority of the observed respiratory events in IPF patients based on the newer studies.…”
supporting
confidence: 65%
“…Data by Lancaster et al [5] show an increased incidence of OSA in IPF patients. Forty-four of 50 subjects (88%) had OSA as defined by an AHI of >5 events per hour.…”
mentioning
confidence: 92%
“…These sleep disturbances had an effect on the subjective state/functionality, as measured by FOSQ and Pittsburgh (PSQI) [3]. Only recently, polysomnographic studies on the incidence of obstructive sleep apnea (OSA) in pulmonary fibrosis have been published [4,5].Data by Lancaster et al [5] show an increased incidence of OSA in IPF patients. Forty-four of 50 subjects (88%) had OSA as defined by an AHI of >5 events per hour.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Obstructive sleep apnea (OSA) is a common disease with substantial health and economic impact [1][2][3]. During sleep, the upper airway collapses repeatedly leading to sleep fragmentation and oxyhemoglobin desaturation.
…”
mentioning
confidence: 99%